A multi-scale analysis of stress distribution in thin composite plates with dense system of ribs in two directions. (March 2021) - Marczak, Jakub; Michalak, Bohdan; Wirowski, Artur
Highlights: A static analysis of plate with a dense system of ribs in two directions is considered. The behaviour of the structure is expressed with a similar equation as a classic thin plate. The software, which automatically evaluate all coefficients of such equation, has been written in C ++ environment. Comparative simulations with FEM proved the convenience and accuracy of the proposed model. A two-scale modelling algorithm is used in the stress distribution analysis.